The Mediating Role of Academic Engagement in the Relationship Between Goal Orientation, Academic Burnout, and Academic Procrastination - Dehghani, Mojgan; Mohammadpanah Ardakan, Azra; Aryanpour, Hamid Reza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to explain the mediating role of academic engagement in the relationship between goal orientation, academic burnout, and academic procrastination among high school students.Methods and Materials: The research method was descriptive and correlational. The statistical population included all female high school students in Ardakan County during the 2020-2021 academic year. A sample of 294 students was selected using convenience sampling based on the Morgan table. The instruments used in this study were the Solomon and Rothblum Academic Procrastination Questionnaire (1984), the Breso et al. Academic Burnout Questionnaire (1997), the Elliot and McGregor Goal Orientation Questionnaire (2001), and the Fredricks et al. Academic Engagement Questionnaire (2004).Findings: The results showed a positive and significant relationship between academic engagement and the variables of mastery-approach and performance-approach. There was an inverse and significant relationship between academic engagement and the variables of mastery-avoidance and performance-avoidance. Academic engagement had an inverse and significant relationship with academic procrastination and academic burnout. The indirect relationships of mastery-approach and performance-approach variables through academic engagement with academic procrastination and academic burnout were inverse and significant. The indirect relationships of mastery-avoidance and performance-avoidance variables through academic engagement with academic procrastination and academic burnout were positive and significant (p < .05).Conclusion: Based on the findings of this study, it can be concluded that academic engagement influences goal orientation, academic procrastination, and academic burnout. It is suggested that planners, officials, and counselors in the education system take the necessary actions to foster academic engagement.